An amyloidogenic sequence at the N-terminus of the androgen receptor impacts polyglutamine aggregation - Oppong, Emmanuel (Biomolecules, 2017)
We present evidence for a crosstalk between the amyloidogenic properties of the KELCKAVSVSM motif and the polyQ stretch at the AR-NTD.